2014
DOI: 10.4238/2014.january.29.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antithrombotic therapy in elderly patients with atrial fibrillation

Abstract: ABSTRACT.This study aimed to analyze the impact factors and outcome of antithrombotic therapy in elderly patients over 65 years old that suffered from atrial fibrillation (AF). A total of 256 elderly patients with AF over 65 years old were divided into 3 groups: 65-74 years old (N = 86), 75-84 years old (N = 122), and over 85 years old (N = 48). The clinical characteristics, antithrombotic therapy, and its related impact factors were retrospectively analyzed. Of all patients, 187 received antithrombotic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Adapted from: Lubitz et al, 1 Go et al, 2 Heeringa et al, 3 Barrios et al, 4 Gómez-Doblas et al, 5 Baena-Díez et al, 6 López Soto et al, 7 Rodríguez-Mañero et al, 8 Barrios et al, 9 Freedman et al, 10 Mérida-Rodrigo et al, 11 Hanon et al, 12 Rønning et al, 16 Camm et al, 17 Camm et al, 18 Pisters et al, 19 Lip et al, 20 Mant et al, 26 Lip and Lane, 27 Siu and Tse, 28 Formiga et al, 30 Gage et al, 31 Gao et al, 32 Darnell et al 33 and Fuenzalida et al 34 intracranial and extracranial bleeding in the participants younger than 75 years. The patients aged 75 years or older had less frequent intracranial bleeding, but the extracranial bleeding was equal or more frequent.…”
Section: Direct Oral Anticoagulants In Elderly Patientsmentioning
confidence: 99%
“…Adapted from: Lubitz et al, 1 Go et al, 2 Heeringa et al, 3 Barrios et al, 4 Gómez-Doblas et al, 5 Baena-Díez et al, 6 López Soto et al, 7 Rodríguez-Mañero et al, 8 Barrios et al, 9 Freedman et al, 10 Mérida-Rodrigo et al, 11 Hanon et al, 12 Rønning et al, 16 Camm et al, 17 Camm et al, 18 Pisters et al, 19 Lip et al, 20 Mant et al, 26 Lip and Lane, 27 Siu and Tse, 28 Formiga et al, 30 Gage et al, 31 Gao et al, 32 Darnell et al 33 and Fuenzalida et al 34 intracranial and extracranial bleeding in the participants younger than 75 years. The patients aged 75 years or older had less frequent intracranial bleeding, but the extracranial bleeding was equal or more frequent.…”
Section: Direct Oral Anticoagulants In Elderly Patientsmentioning
confidence: 99%
“…Of course, this is a single center study and our findings must be confirmed in further investigations but our data are also in line with further descriptions of less commitment on the treatment of old patients; an obviously frequent finding in cardiovascular disease. For example, there was a rare secondary cardiovascular preventive therapy in elderly [34] an undertreatment with oral anticoagulation [35] [36], the finding that advancing age was inversely associated with receipt of evidence-based cardiac therapies following acute myocardial infarction [37] and the observation that elderly patients were less likely to receive evidence-based treatments in heart failure [38].…”
Section: In-hospital Findingsmentioning
confidence: 99%